2014
DOI: 10.1016/j.annemergmed.2013.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Severity-Adjusted Mortality in Trauma Patients Transported by Police

Abstract: Study objective Two decades ago, Philadelphia began allowing police transport of patients with penetrating trauma. We conduct a large, multiyear, citywide analysis of this policy. We examine the association between mode of out-of-hospital transport (police department versus emergency medical services [EMS]) and mortality among patients with penetrating trauma in Philadelphia. Methods This is a retrospective cohort study of trauma registry data. Patients who sustained any proximal penetrating trauma and prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
96
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 86 publications
(105 citation statements)
references
References 28 publications
(30 reference statements)
9
96
0
Order By: Relevance
“…Previous studies have inappropriately reported protective effects from alcohol and adjusted for injury whereas the results from this study examined injury mechanism and severity separately as intermediate outcomes from alcohol exposure 7–9, 25 . In a previous study, gunshot wounds had a three-fold higher proportion of deaths than stab wounds in a large trauma cohort 26 . Similarly, the moderate BAC group in this study had the highest odds for in-hospital death with a greater proportion of penetrating injuries, mainly gunshot wounds, than any other group.…”
Section: Discussionmentioning
confidence: 77%
“…Previous studies have inappropriately reported protective effects from alcohol and adjusted for injury whereas the results from this study examined injury mechanism and severity separately as intermediate outcomes from alcohol exposure 7–9, 25 . In a previous study, gunshot wounds had a three-fold higher proportion of deaths than stab wounds in a large trauma cohort 26 . Similarly, the moderate BAC group in this study had the highest odds for in-hospital death with a greater proportion of penetrating injuries, mainly gunshot wounds, than any other group.…”
Section: Discussionmentioning
confidence: 77%
“…24 Studies also have shown that in cases of penetrating trauma, decreased time to definitive care is associated with improved survival outcomes. [25][26][27] Conclusions The current case series demonstrates the life-saving potential for law enforcement personnel trained and equipped under current TCCC/C-TECC tactical casualty care guidelines. Although originally developed to save the lives of wounded combat personnel, in the civilian sector, the training is more likely to save victims rather than law enforcement personnel.…”
Section: Limitationsmentioning
confidence: 76%
“…Conveyance by ambulance or police units to trauma centers does not appear to influence victim injury severity or mortality (Band, Salhi, Holena, et al, 2014), but victims who are transported by private, non-emergency means tend to have better survival outcomes relative to victims who delivered to trauma centers by emergency services (Demetriades et al, 1996). Consistent with CEP, public health and medical researchers have made significant contributions about the relationship between response processes that occur after a criminal act and victim injury outcomes.…”
Section: Conceptual Frameworkmentioning
confidence: 98%